Social support and resilience in persons with severe haemophilia: An interpretative phenomenological analysis. Issue 3 (14th April 2020) - Ratajová, Kateřina; Blatný, Jan; Poláčková Šolcová, Iva; Meier, Zdeněk; Horňáková, Tekla; Brnka, Robert; Tavel, Peter
Abstract: Introduction: Haemophilia is a hereditary haemorrhagic disorder characterized by deficiency or dysfunction of coagulation factors. Recurrent joint and muscle bleeds lead to progressive musculoskeletal damage. Haemophilia affects patients physically but also socially and psychologically. Traumatic experiences, chronic stress and illnesses can lead to mental disorders, but many persons with haemophilia maintain a highly positive outlook. Aim: To explore qualitatively which coping mechanisms persons with haemophilia use and in what way they help them to live with their diagnosis. Methods: We recruited five adults with haemophilia and conducted semi‐structured face‐to‐face interviews. Transcripts were analysed using interpretative phenomenological analysis (IPA). Results: Two core themes emerged from the analysis: social support as an external factor and resilience as an internal factor of coping with the disease. Persons with haemophilia usually need help with health‐related complications, and this affects the social support they require. Their wider support network tends to involve family and friends but also healthcare professionals and other specialists. This network provides practical help but also functions as an important psychological protective factor. An unexpected finding was that persons with haemophilia want not only to receive support but are also keen to offer support to others. Conclusion: These findings can help identify persons who provide most support to people suffering from haemophilia. Haemophilic centres should include in their teams psychologists and social workers and offer individual and group therapy to their clients, group meetings for friends and families of persons with haemophilia, provide learning resources to teachers aiming to incorporate children with haemophilia in their peer group, and organize Balint groups for physicians, psychologists and other healthcare professionals.